Importance of unified pedagogical process in development of communicative competence for adolescents with language disorders - Svetlana Usca (Social Welfare: Interdisciplinary Approach)
The importance of unifi ed pedagogical process in development of communicative competence is analysed in this article. Necessity for synergy between learning process and extra-curricular activities is emphasized. The article focuses on adolescents with language disorders whose insufficiently developed language impedes the development of communicative competence and constitutes a menace to socialization in the future. The research data have been analysed and processed by SPSS program and AQUAD 6 software.